The Effects of Cobb’s Trauma in Christopher Nolan’s Inception - Evania Nur Aprilla; Cahyaningsih Pujimahanani (Menulis: Jurnal Penelitian Nusantara, 2025)
This study, entitled “The Effects of Cobb’s Trauma in Christopher Nolan’s Inception” aims to explore how trauma shapes the life of the main character, Cobb. Using a qualitative method and Charcot’s theory. The finding show that unresolved trauma dominates Cobb’s mind and behavior, producing deep and long-lasting effects. Coob’s trauma is reflected in psychological conditions such as anxiety and flashbacks, and it also influences his decisions, actions, and relationships. The study concludes that trauma not only affects Cobb’s inner world but also directs the course of his life journey.